Measurement of the total cross section from elastic scattering in pp collisions at s√=8 TeV with the ATLAS detector - Aaboud, M. (2016)
A measurement of the total pp cross section at the LHC at √ s = 8 TeV is presented. An integrated luminosity of 500 µb −1 was accumulated in a special run with high-β ? beam optics to measure the differential elastic cross section as a function of the Mandelstam momentum transfer variable t. The measurement is performed with the ALFA sub-detector of ATLAS. Using a fit to the differential elastic cross section in the −t range from 0.014 GeV2 to 0.1 GeV2 to extrapolate t → 0, the total cross section, σtot(pp → X), is measured via the optical theorem to be σtot(pp → X) = 96.07 ± 0.18 (stat.) ± 0.85 (exp.) ± 0.31 (extr.) mb , where the first error is statistical, the second accounts for all experimental systematic uncertainties and the last is related to uncertainties in the extrapolation t → 0. In addition, the slope of the exponential function describing the elastic cross section at small t is determined to be B = 19.74 ± 0.05 (stat.) ± 0.23 (syst.) GeV−2 .